Perceived organizational support and the relationship between perceptions of organizational politics and organizational outcomes: a case study of two Malaysian organizations / Sharifah Muhairah Shahabudin - Shahabudin, Sharifah Muhairah (2007)
Politics is an essential element of behavioural process in organizational settings (Allen, Madison, Porter, Renwick, & Mayes, 1979). It is believed that the existence of politics create tension and indicate irrational considerations especially when it involves formal organizational processes such as decision and policy making, goal setting and resource allocation (Drory & Romm, 1990; Ferris & Kacmar, 1992). Due to its impact on organizational setting, organizational politics has been studied extensively over the last four decades. This study has adapted and modified the Perceptions of Organizational Politics Model (Ferris, Russ, and Fandt, 1989) and Organizational Image Model (Vigoda, Peretz & Zion, 2003) to examine the relationship between perceptions of organizational politics (i.e., go along to get ahead political attitude and politics in pay and promotion policies) and two organizational outcomes (i.e., organizational image and turnover intention). The current study also investigated the impact of perceived organizational support on the relationship between perceptions of organizational politics and organizational outcomes in two Malaysian IT services related organizations. Triangulation method, a combination of qualitative and quantitative method of data collection was used in the present study. Data was gathered primarily through questionnaire survey and secondly through semi-structured interviews with senior management team. The data was collected within three months with 362 respondents from questionnaire survey and 11 respondents from the interview. The questionnaires that were collected were analyzed using principal components factor analysis with VARIMAX rotation, descriptive statistics, Cronbach Alpha and Pearson Correlation. Hierarchical regression analysis was used to test the relationship between perceptions of organizational politics with the organizational outcomes and the moderator. Three personal variables (age, gender and organizational tenure) were controlled in the statistical analyses to reduce the possibility of spurious relationships. It was found only age had a significant effect on the impact or perceptions of organizational politics on turnover intentions. Results generally indicated that the relationship between perceptions of organizational politics and organizational image is inversely related, while the relationship with turnover intention is positively related. The findings also indicated that it is in line with other studies conducted in Malaysia (Poon, 2003, Rusinah, et. al, 2003), employees, in general perceived organizational politics as having a negative effect on the organization and that heightened perceptions of organizational politics will result in turnover intentions. The findings of the present study found that perceived organizational support has a moderating effect on the relationship between go along to get ahead and organizational image as well as the relationship between pay and promotion policies and turnover intentions. These results suggest the critical role of perceived organizational support to reduce turnover intentions and in fostering good organizational image.